Prophylaxis and Therapy of Venous Thrombotic Events (VTE) in Pregnancy and the Postpartum Period - Sucker, Christoph (Geburtshilfe und Frauenheilkunde, 2020)
Venous thromboembolisms and pulmonary embolisms are one of the main causes of morbidity and mortality in pregnancy. The increased risk of thrombotic events caused by the physiological changes during pregnancy alone does not justify any medical antithrombotic prophylaxis. However, if there are also other risk factors such as a history of thromboses, hormonal stimulation as part of fertility treatment, thrombophilia, increased age of the pregnant woman, severe obesity or predisposing concomitant illnesses, the risk of thrombosis should be re-evaluated – if possible by a coagulation specialist – and drug prophylaxis should be initiated, where applicable. Low-molecular-weight heparins (LMWH) are the standard medication for the prophylaxis and treatment of thrombotic events in pregnancy and the postpartum period. Medical thrombosis prophylaxis started during pregnancy is generally continued for about six weeks following delivery due to the risk of thrombosis which peaks during the postpartum period. The same applies to therapeutic anticoagulation after the occurrence of a thrombotic event in pregnancy; here, a minimum duration of the therapy of three months should also be adhered to. During breastfeeding, LMWH or the oral anticoagulant warfarin can be considered; neither active substance passes into breast milk.Venöse Thromboembolien und Lungenembolien sind eine der Hauptursachen von Morbidität und Mortalität in der Schwangerschaft. Das durch die physiologischen Veränderungen während der Schwangerschaft bedingte erhöhte Risiko thrombotischer Ereignisse rechtfertigt alleine noch keine medikamentöse antithrombotische Prophylaxe. Kommen allerdings weitere Risikofaktoren wie Thrombosen in der Vorgeschichte, hormonelle Stimulation im Rahmen einer Kinderwunschbehandlung, Thrombophilie, höheres Schwangerenalter, gravierendes Übergewicht oder prädisponierende Begleiterkrankungen hinzu, muss das Thromboserisiko – nach Möglichkeit von einem Gerinnungsspezialisten – neu bewertet und gegebenenfalls eine medikamentöse Prophylaxe eingeleitet werden. Niedermolekulare Heparine (NMH) sind die Standardmedikation zur Prophylaxe und Therapie thrombotischer Ereignisse in Schwangerschaft und Wochenbett. Eine in der Schwangerschaft begonnene medikamentöse Thromboseprophylaxe wird aufgrund des im Wochenbett gipfelnden Thromboserisikos in der Regel für ca. 6 Wochen nach der Entbindung fortgeführt. Gleiches gilt für die therapeutische Antikoagulation nach Auftreten eines thrombotischen Ereignisses in der Schwangerschaft; hier sollte auch eine Mindestdauer der Therapie von 3 Monaten eingehalten werden. In der Stillzeit kommen NMH oder das orale Antikoagulans Warfarin in Betracht; beide Wirkstoffe gehen nicht in die Muttermilch über.
Keywords: thromboembolisms; pregnancy; anticoagulation; low-molecular-weight heparins; oral anticoagulants